1969
DOI: 10.1021/ja01039a007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the intramolecular four-center elimination of isobutylene from triisobutylaluminum in the gas phase

Abstract: The gas-phase kinetics and the mechanistics of the unimolecular elimination of isobutylene from triisobutylaluminum have been studied in the presence of excess ethylene or 1-butene for temperatures ranging from 107 to 173°. The 1-alkenes reacted very fast with the diisobutylaluminum hydride formed in the elimination process, thus avoiding complications from back and side reactions. The reaction is apparently homogeneous, when carried out in an all-Teflon reaction vessel. The computed least-squares analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 0 publications
3
32
0
Order By: Relevance
“…The cleaved N-N bond of both 4 and 5 was confirmed by 15 N NMR spectroscopy using ([NPN]Ta) 2 (µ-η 1 :η 2 -15 N 2 )(µ-H) 2 , 15 N 2 -1, in the reaction with DIBAL. The resulting 15 N-labeled materials both showed resonances that did not display 25,26 and has only one isobutyl group at the Al center (eq 2). Migration of a ligand amide from Ta to Al, reductive elimination of H 2 , and N-N bond cleavage complete the overall scheme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cleaved N-N bond of both 4 and 5 was confirmed by 15 N NMR spectroscopy using ([NPN]Ta) 2 (µ-η 1 :η 2 -15 N 2 )(µ-H) 2 , 15 N 2 -1, in the reaction with DIBAL. The resulting 15 N-labeled materials both showed resonances that did not display 25,26 and has only one isobutyl group at the Al center (eq 2). Migration of a ligand amide from Ta to Al, reductive elimination of H 2 , and N-N bond cleavage complete the overall scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Diisobutylaluminum deuteride was prepared by literature methods. 26 Ethylene, propylene (Praxair), and acetylene (Matheson) were used as obtained from commercial gas suppliers. Phenylacetylene was distilled prior to preparation of a toluene solution of known concentration, which was used in synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the reaction involves formation of a symmetric π-complex intermediate leading to the formation of addition product via a four-centered transition state. Experimental work by Egger supports these results 17 . The alternative π-complex transition state proposed by Eisch 18 ; however, is inconsistent with both the theoretical studies and the experimental work of Egger 17 .…”
Section: Introductionmentioning
confidence: 65%
“…Experimental work by Egger supports these results 17 . The alternative π-complex transition state proposed by Eisch 18 ; however, is inconsistent with both the theoretical studies and the experimental work of Egger 17 . In 1981, Grophen and Haaland characterized the transition structure for the addition of acetylene into the Al-H bond of alane 19 .…”
Section: Introductionmentioning
confidence: 65%
“…Exploratory work by Egger supports these results. 17 The alternative π-complex transition state proposed by Eisch;…”
Section: −15mentioning
confidence: 99%